2015
DOI: 10.1007/s10439-014-1230-2
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial Creep Resistance and Structural Remodeling of the Aortic and Mitral Valves in Pregnancy

Abstract: Pregnancy produces rapid, dramatic volume-overload changes to the maternal circulation. This paper examines pregnancy-induced structural-mechanical changes in bovine aortic and mitral heart valve leaflets. Valve leaflets were harvested from non-pregnant heifers and pregnant cows. Dimensions, biaxial extensibility and creep resistance were assessed and related to changes in the collagen network: histological leaflet and anatomic layer thicknesses plus collagen crimp, and biochemical collagen content. Collagen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 34 publications
9
41
0
Order By: Relevance
“…Note that mass fractions of collagen and elastin were not included in the set of estimated parameters, and were instead prescribed from previous biochemical assay results [5,14]. Mass fraction data were re-analysed to identify potential timedependent trends, and appropriate values for f c and f e were assigned to each specimen accordingly.…”
Section: Parameter Estimationmentioning
confidence: 99%
“…Note that mass fractions of collagen and elastin were not included in the set of estimated parameters, and were instead prescribed from previous biochemical assay results [5,14]. Mass fraction data were re-analysed to identify potential timedependent trends, and appropriate values for f c and f e were assigned to each specimen accordingly.…”
Section: Parameter Estimationmentioning
confidence: 99%
“…Many investigations of valve adaptation have focused on physiological development (8,20,(51)(52)(53) or pathological conditions such as left ventricular (LV) dysfunction (10), mitral valve regurgitation (58), myxomatous degeneration (19), or heart failure (17). Recent studies from our laboratory, however, have demonstrated the capacity of maternal heart valve leaflets to remodel under the altered hemodynamics of pregnancy, a nonpathological condition (38,39,60). Pregnancy is accompanied by an increase in blood volume and cardiac output of ϳ50%, as the maternal circulation accommodates the developing fetoplacental unit.…”
mentioning
confidence: 99%
“…These changes in geometry then elevate stresses on closed valve leaflets per the Law of Laplace (26). Our studies of the aortic and mitral valves have thus far shown dramatic increases in leaflet size of both valves accompanied by alterations in fiber architecture and composition, a decrease in thermal stability of collagen, a reversible shift in leaflet extensibility, and valve-specific alterations in resistance to creep (38,39,60). Together, these results provide strong evidence of both collagen turnover during pregnancy and unexpected maturation of native leaflet collagen, a complex restructuring of the collagen matrix under the altered cardiovascular loading and hormonal shifts of pregnancy.…”
mentioning
confidence: 99%
See 2 more Smart Citations